Methods in consumer research - Ares, Gaston; Varela, Paula (Woodhead Publishing Series in Food Science, Technology and Nutrition, 2018)
Methods for Consumer Research, Volume One: New Approaches to Classic Methods brings together world leading experts in global consumer research who provide a fully comprehensive state-of-the-art coverage of advances in the classical methods of consumer science. The book touches on the latest developments in qualitative techniques, including coverage of both focus groups and social media, while also focusing on liking, a fundamental principle of consumer science, consumer segmentation, and the influence of extrinsic product characteristics, such as packaging and presentation on consumer liking.